The Nadars of Tamilnad : The Political Culture of a Community in Change - Hardgrave, Robert L. (Brill | Manohar Publishers & Distributors, 2024)
Among the various communities of South India, the Nadars have perhaps most clearly evidenced the impact of change over the past 200 years. Considered by high-caste Hindus in the early nineteenth century to be of extremely low status, the Nadars-toddy-tappers, climbers of the palmyra palm-suffered severe social disabilities and were among the most depressed communities in the Tamil country. Because of their sensitive response to social and economic change over the past century and a half, the Nadars have today become one of the most successful groups in the South, in both economic and political terms, and considerable command respect. From among their numbers have come leaders in business, industry, and the professions; and in politics, Kamaraj, their illustrious son, brought fame to the caste as Chief Minister of Madras and as President of the Indian National Congress. The Nadars have had a turbulent and colourful history. Their struggle to rise above their depressed condition assumed dramatic forms in a series of escalating confrontations between the caste and its antagonists. From the breast-cloth controversy through the sack of Sivakasi to the Nadar Mahajana Sangam, the Nadars' rise, exemplifying the processes of mobilization in Indian society, provides rich material for an analysis of the political life of a community in change. When the book was first published in 1969, Lloyd Rudolph wrote, 'Hardgrave illuminates in ways hitherto unexplored the processes of social and political change that have so profoundly affected India. I judge his book to be one of the most important and exciting studies in the Indian field in recent years'. With this reissue, The Nadars of Tamilnad is again available, and its compelling portrayal of a caste in transition stands as, one reviewer wrote, 'one of the landmarks in South Indian social history'.